Method for preparing lactic acid through electrocatalysis cathode and anode coupling

Through the electrocatalytic catalytic anode coupling method, a single metal/bimetal based catalyst is used to carry out oxidation reactions in the anode and cathode respectively, solving the problems of low energy efficiency and poor catalyst stability in the prior art 1,2-propylene glycol electrocatalytic oxidation of lactic acid in the prior art. , the effect of efficient preparation of lactic acid at room temperature and pressure is achieved.

CN119243182AActive Publication Date: 2025-01-03DALIAN UNIV OF TECH

Patent Information

Application Number
CN202411675767.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-22
Publication Date
2025-01-03
Estimated Expiration
2044-11-22

AI Technical Summary

Technical Problem

The existing 1,2-propanediol electrocatalytic oxidation method for lactic acid is low in energy efficiency under simple anode oxidation, and the catalyst stability is poor, which limits large-scale production. Thermal catalytic method is limited by high temperature and high pressure environment, making it difficult to prepare efficiently under mild conditions. Lactic acid.

Method used

Using the electrocatalytic cathodic anode coupling method, a single metal/bimetal based catalyst is used to perform oxidation reactions on the anode and cathode respectively. By anodizing 1,2-propanediol and using the hydroxyl radicals generated by the electrofenton reaction at the cathode, oxygen and Co-conversion of 1,2-propylene glycol prepared lactic acid and was carried out at room temperature and pressure.

Benefits of technology

It has achieved efficient preparation of lactic acid under high current density, improved the overall yield and energy utilization rate of lactic acid, improved the efficiency of co-conversion of yin and yang poles to produce lactic acid, and has broad application prospects.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119243182A_ABST
    Figure CN119243182A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of lactic acid production, and discloses a method for preparing lactic acid by electrocatalytic cathode and anode coupling, which comprises the following steps: assembling an anode catalyst as an anode, a cathode catalyst as a cathode and an electrolyte into an electrolytic tank; 1, 2-propylene glycol is added into the anolyte and the catholyte respectively; under the application of a certain voltage, 1, 2-propylene glycol is oxidized into lactic acid at the anode end; oxygen is continuously introduced into the catholyte, meanwhile, a ferrous compound is additionally added into the catholyte for catalysis to form hydroxyl free radicals, and electro-conversion of 1, 2-propylene glycol and oxygen is achieved through an electro-Fenton reaction to prepare lactic acid. Compared with single-side anodic oxidation, the method has the advantages that the energy utilization rate is increased, and a new thought and method are provided for green and efficient preparation of lactic acid at normal temperature, normal pressure and high current density.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of lactic acid production and relates to a method for preparing lactic acid by electrocatalytic anode- cathode coupling. Background Art

[0002] 1,2-propylene glycol is a common organic compound. With the increasing demand for sustainable development and environmental protection, the bio-based route has gradually become an important source for the production of 1,2-propylene glycol. This method uses renewable biomass as raw materials and utilizes biocatalysis and chemical processes to produce 1,2-propylene glycol. Glycerol is a by-product in the production of biodiesel. 1,2-propylene glycol can be produced by hydrogenating glycerol. The selective oxidation of 1,2-propylene glycol has always been a hot topic of research. The oxidation products of 1,2-propylene glycol include formic acid, acetic acid, lactic acid, hydroxyacetone, etc.

[0003] Lactic acid is an important high value-added fine chemical. It is widely used as a monomer for the production of biodegradable polymer polylactic acid. It is also widely used in the pharmaceutical and agrochemical fields. Currently, microbial fermentation is the main method for lactic acid production, accounting for about 90% of global production, but this method is time-consuming and subsequent separation is difficult. The thermal catalytic reaction rate of glycerol to lactic acid is fast and has high lactic acid selectivity. However, the further development of thermal catalytic strategies is limited by high temperature and high pressure environments. Therefore, it remains a huge challenge to use a sustainable method to efficiently prepare lactic acid under mild conditions.

[0004] So far, the electrocatalytic oxidation of 1,2-propylene glycol to lactic acid reported in the literature is still a simple anodic extreme oxidation, which has low energy efficiency. The most commonly used catalyst is a powder catalyst, which has a low current density (<100mA cm -2 )(ACS Catal. 2015, 5(11), 6926–6936.), but problems such as complex synthesis and poor stability limit their large-scale production. Summary of the invention

[0005] The present invention is proposed to overcome the shortcomings of the existing 1,2-propylene glycol oxidation to lactic acid, and its purpose is to provide a method for preparing lactic acid by electrocatalytic anode- cathode coupling, so as to achieve green, efficient and high current density preparation of lactic acid under normal temperature and pressure conditions, and has the advantage of high energy utilization, thereby increasing the overall yield of lactic acid.

[0006] The technical solution of the present invention:

[0007] A method for preparing lactic acid by electrocatalytic cathode-cathode coupling, comprising the following steps:

[0008] (1) Assembling an electrolytic cell: using the anode catalyst as the anode and the cathode catalyst as the cathode, placing the anode and the cathode in corresponding electrolytes respectively, and assembling an electrolytic cell;

[0009] (2) Electrocatalytic reaction: 1,2-propylene glycol is added to both the anolyte and the catholyte. Under the application of a certain voltage, 1,2-propylene glycol is oxidized to lactic acid at the anode end. Oxygen is continuously introduced into the catholyte, and additional divalent iron compounds are added to the electrolyte to catalyze the formation of hydroxyl radicals, thereby achieving the electrochemical conversion of 1,2-propylene glycol and oxygen to produce lactic acid.

[0010] The anode catalyst is one of single metal / conductive substrate, bimetal / conductive substrate, bimetal / hydroxide, bimetal / oxide, or a combination of two or more thereof, wherein the hydroxide is one of nickel-based, cobalt-based, copper-based, and iron-based hydroxides; and the oxide is one of nickel oxide, cobalt oxide, iron oxide, and copper oxide.

[0011] The metal on the anode catalyst is one or a combination of two of platinum, gold, silver, ruthenium, palladium and copper.

[0012] The conductive substrate is one of carbon cloth, carbon paper, foam nickel, nickel mesh, foam copper and copper mesh.

[0013] The divalent iron compound is at least one of ferrous sulfate, ferrous nitrate and ferrous oxalate.

[0014] The anolyte is any one aqueous solution of sodium hydroxide, potassium hydroxide, lithium hydroxide, potassium bicarbonate, potassium carbonate, sodium bicarbonate, and sodium carbonate, and the concentration is 0.1-2M.

[0015] The cathode electrolyte is at least one of perchloric acid, sulfuric acid and sodium bisulfate solution, and the concentration is 0.1-1M.

[0016] The conditions of the electrocatalytic reaction in step (2) are normal temperature and pressure, and the anode voltage is 0.3V to 1.5V vs. RHE.

[0017] The concentration of the divalent iron compound applied in step (2) is 0.05-50 mM, preferably 2 mM.

[0018] The oxygen flow rate introduced in step (2) is 10-50 mL / min, preferably 20 mL / min.

[0019] The beneficial effects of the present invention are as follows: the present invention provides a method for preparing lactic acid by electrocatalytic anode-cathode coupling, constructs a single metal / bimetallic-based catalyst as an anode-cathode catalyst, uses water molecules as an oxygen source in the oxidation end reaction, utilizes an electrocatalytic method driven by renewable energy to oxidize 1,2-propylene glycol to lactic acid at the anode, and simultaneously uses hydroxyl radicals generated by the electro-Fenton reaction at the cathode end to oxidize 1,2-propylene glycol, thereby achieving co-conversion of oxygen and 1,2-propylene glycol to prepare lactic acid, and the efficiency of co-conversion of anode and cathode to generate lactic acid is higher than that of unilateral conversion.

[0020] In summary, the present invention can realize the production of lactic acid by coupling anode and cathode, and has broad application prospects. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 It is a schematic diagram of the principle of producing lactic acid by electrocatalytic cathode-cathode coupling of the present invention;

[0022] Figure 2 is a scanning electron microscope image of the catalyst in Example 1 of the present invention;

[0023] Figure 3 is a linear polarization curve diagram of electrocatalytic oxidation of 1,2-propylene glycol by different bimetallic anode catalysts in Example 1 of the present invention;

[0024] Figure 4 This is the NMR spectrum of the 1,2-propylene glycol oxidation product at the anode end in Example 1 of the present invention.

[0025] Figure 5 This is the NMR spectrum of the product of the co-conversion of 1,2-propylene glycol and oxygen at the cathode end in Example 1 of the present invention.

[0026] Figure 6 is a scanning electron microscope image of the catalyst in Example 2 of the present invention;

[0027] Figure 7 It is a linear polarization curve diagram of the electrocatalytic oxidation of 1,2-propylene glycol by the catalyst in Example 2 of the present invention.

[0028] Figure 8 is a scanning electron microscope image of the catalyst in Example 3 of the present invention;

[0029] Fig. 9 is the XRD pattern of the catalyst in Example 3 of the present invention;

[0030] Fig.10 is a linear polarization curve diagram of the electrocatalytic anodic extreme oxidation of 1,2-propylene glycol in Example 3 of the present invention;

[0031] Fig.11 It is a performance diagram of the catalyst in Example 3 of the present invention at different oxidation potentials for electrocatalytic anodic extreme oxidation of 1,2-propylene glycol.

[0032] Fig.12 It is a comparison chart of the lactic acid production rates of anode-cathode coupling and simple anodic oxidation in Example 4 of the present invention. DETAILED DESCRIPTION

[0033] The specific implementation of the present invention is further described below in conjunction with the accompanying drawings and technical solutions.

[0034] Example 1

[0035] Electrocatalytic cathode-cathode coupling to produce lactic acid:

[0036] (1) Preparation of Catalyst

[0037] ① Preparation of nickel foam loaded AuPt alloy catalyst by electroplating

[0038] First, the nickel foam is pretreated. The specific method is as follows: first, the nickel foam is ultrasonically treated in acetone for 15 minutes, rinsed with deionized water, then ultrasonically treated in dilute hydrochloric acid (3M) for 15 minutes, rinsed with deionized water, and finally ultrasonically treated in deionized water for 15 minutes and then quickly dried to obtain the pretreated nickel foam.

[0039] Then, a layer of nickel hydroxide was loaded on the surface of the nickel foam. The specific method was as follows: 50 mg of nickel chloride hexahydrate, 50 mg of urea and 15 ml of deionized water were transferred to a 50 ml hydrothermal kettle and kept at 150 ° C for 12 hours. The nickel foam was taken out and then rinsed with deionized water to obtain (Ni(OH)2 / Ni foam), and then AuPt alloy was loaded. The specific method was as follows: a mixed solution of 5 mM chloroauric acid and 5 mM chloroplatinic acid was prepared, and 50 mM hexadecyltrimethylammonium bromide was added. The pretreated nickel foam was used as the working electrode, the nickel foam was used as the counter electrode, and the saturated calomel electrode was used as the reference electrode to form a three-electrode system. At 5 mA cm -2 The anode nickel foam loaded with AuPt alloy (AuPt / Ni(OH)2) was obtained by constant current cathode electrodeposition at a current density of 1.50 for 20 min, and then polarized in 1 M KOH to generate nickel oxyhydroxide. The specific method is: cyclic voltammetry was performed on an electrochemical workstation with a scan rate of 100 mV s -1 , cycled 20 times in the voltage range of 0V~0.8V vs.Ag / AgCl to obtain (AuPt / NiOOH).

[0040] The scanning electron microscopy image of the obtained catalyst AuPt / NiOOH is as follows Figure 2 As shown by Figure 2 It can be seen that the AuPt alloy has a granular morphology.

[0041] (2) Electrolyte configuration

[0042] The electrolyte at the anode end was a mixed solution of 50 mM 1,2-propylene glycol and 1 M potassium hydroxide.

[0043] The cathode electrolyte was a mixed solution of 50 mM 1,2-propylene glycol, 0.3 M sodium bisulfate, and 2 mM ferrous sulfate.

[0044] (3) Electrocatalytic reaction

[0045] The anode terminal directly applies an oxidation potential of 1.1V vs. RHE. Figure 3 This is the linear polarization curve of the electrocatalytic oxidation of 1,2-propylene glycol by the anode catalyst. It can be seen from the linear polarization curve that at an oxidation potential of 1.1 V vs. RHE, the AuPt / NiOOH catalyst can reach more than 250 mA cm -2 of current density.

[0046] Oxygen was introduced into the cathode end at a flow rate of 20 mL / min.

[0047] (4) Product testing

[0048] After the reaction, 300 μl of electrolyte was extracted from each end of the cathode and cathode, and then 100 μl of deuterated water, 200 μl of water, and 50 μl of DMSO (2 mM) were added. The samples were placed in a nuclear magnetic resonance tube for nuclear magnetic resonance detection. The results of nuclear magnetic resonance detection were Figure 4 This indicates that lactic acid is generated in the anode products. Figure 5 This indicates that lactic acid is also generated in the cathode product.

[0049] Example 2

[0050] (1) Preparation of Catalyst

[0051] ① Preparation of nickel foam loaded Au catalyst by hydrothermal method

[0052] First, the nickel foam is pretreated. The specific method is as follows: first, the nickel foam is ultrasonically treated in acetone for 15 minutes, rinsed with deionized water, then ultrasonically treated in dilute hydrochloric acid (3M) for 15 minutes, rinsed with deionized water, and finally ultrasonically treated in deionized water for 15 minutes and then quickly dried to obtain the pretreated nickel foam.

[0053] Then, prepare 20mM chloroauric acid, add 3ml of the prepared chloroauric acid into a 20ml glass bottle, add 30mg of polyether, add 50μl of ethanol and 50μl of hydrochloric acid (6M), and then put in 1cm*2cm*1mm foamed nickel. Leave it at room temperature for 12h, take it out and rinse it repeatedly with deionized water and ethanol, quickly vacuum dry it for use, and you can get Au / Nifoam catalyst.

[0054] The scanning electron microscopy image of the obtained anode catalyst Au / Ni foam is as follows Figure 6 As shown by Figure 6 It can be seen that the Au / Nifoam catalyst has a dendritic morphology.

[0055] (2) Electrolyte configuration

[0056] The electrolyte at the anode end was a mixed solution of 50 mM 1,2-propylene glycol and 1 M potassium hydroxide.

[0057] The cathode electrolyte was a mixed solution of 50 mM 1,2-propylene glycol, 0.3 M sulfuric acid, and 2 mM ferrous sulfate.

[0058] (3) Electrocatalytic reaction

[0059] Figure 7 This is the linear polarization curve of the electrocatalytic oxidation of 1,2-propylene glycol by the anode catalyst. It can be seen from the linear polarization curve that at an oxidation potential of 1.25V vs. RHE, the Au / Ni foam catalyst can reach more than 150mA cm -2 of current density.

[0060] Oxygen was introduced into the cathode end at a flow rate of 20 mL / min.

[0061] (4) Product testing

[0062] After the reaction is completed, 300 μL of electrolyte is drawn from both ends of the cathode and cathode respectively, and 100 μL of deuterated water is added, followed by 200 μL of water and 50 μL of DMSO (2 mM), and the mixture is placed in a nuclear magnetic resonance tube for nuclear magnetic resonance detection.

[0063] Example 3

[0064] (1) Preparation of Catalyst

[0065] ① Preparation of nickel foam supported AuPt alloy catalyst by hydrothermal method

[0066] First, the nickel foam is pretreated. The specific method is as follows: first, the nickel foam is ultrasonically treated in acetone for 15 minutes, rinsed with deionized water, then ultrasonically treated in dilute hydrochloric acid (3M) for 15 minutes, rinsed with deionized water, and finally ultrasonically treated in deionized water for 15 minutes and then quickly dried to obtain the pretreated nickel foam.

[0067] Then, prepare 20mM chloroauric acid and 20mM chloroplatinic acid, add 2.25ml of the prepared chloroauric acid and 0.75ml of chloroplatinic acid into a 20ml glass bottle, add 30mg of polyether, add 50μl of ethanol and 50μl of hydrochloric acid (6M), and then put in 1cm*2cm*1mm nickel foam, leave it at room temperature for 12h, take it out and rinse it repeatedly with deionized water and ethanol, quickly vacuum dry it for use, and you can get AuPt / Ni foam catalyst.

[0068] The scanning electron microscopy image of the obtained anode catalyst AuPt / Ni foam is shown in Figure 8 As shown by Figure 8 It can be seen that the AuPt / Nifoam catalyst has a nanoflower morphology. The XRD test results of the catalyst are as follows Fig. 9 As shown in the spectrum, it can be concluded that the catalyst corresponds to Pt 0.2 Au 0.8 alloy phase.

[0069] (2) Electrolyte configuration

[0070] The electrolyte at the anode end was a mixed solution of 50 mM 1,2-propylene glycol and 1 M potassium hydroxide.

[0071] The cathode electrolyte was a mixed solution of 50 mM 1,2-propylene glycol, 0.3 M perchloric acid, and 2 mM ferrous sulfate.

[0072] (3) Electrocatalytic reaction

[0073] Fig.10 This is the linear polarization curve of the electrocatalytic oxidation of 1,2-propylene glycol by the anode catalyst. It can be seen from the linear polarization curve that at an oxidation potential of 0.9V vs. RHE, the AuPt / Ni foam catalyst can reach more than 350mAcm -2 of current density.

[0074] (4) Product testing

[0075] At an oxidation potential of 0.4 V vs. RHE, after one hour of constant potential electrolysis, 300 μL of electrolyte was extracted, 100 μL of deuterated water was added, 200 μL of water was added, and 50 μL of DMSO (2 mM) was added. The mixture was placed in a nuclear magnetic resonance tube for nuclear magnetic resonance detection. The results of the detection and calculation are shown in the figure below. Fig.11 As shown, it can be shown that the lactic acid selectivity at the anode end is greater than 80%.

[0076] Example 4

[0077] (1) Electrode solution configuration

[0078] Control group 1: The electrolyte at the anode end was a mixed solution of 50 mM 1,2-propylene glycol and 1 M potassium hydroxide. The electrolyte at the cathode end was 1 M potassium hydroxide, and the volume of the electrolytes at the cathode and cathode was 30 ml.

[0079] Control group 2: The electrolyte at the anode end was a mixed solution of 50 mM 1,2-propylene glycol and 1 M potassium hydroxide. The electrolyte at the cathode end was a mixed solution of 50 mM 1,2-propylene glycol, 0.3 M sodium bisulfate, and 2 mM ferrous sulfate. The volume of the cathode and cathode electrolytes was 30 ml.

[0080] (2) Electrocatalyst

[0081] The nickel foam loaded AuPt alloy catalyst prepared in Example 3 was used as the anode and cathode.

[0082] (3) Electrocatalytic reaction

[0083] A cell voltage of 1V was applied to the electrolytic cells of control group 1 and control group 2 as a whole, and constant potential electrolysis was performed for two hours. No oxygen was introduced into the cathode of control group 1; oxygen was introduced into the cathode of control group 2 at a flow rate of 20 ml / min for two hours. A cyclic stability test was performed. After the two-hour electrolysis was completed, the test was continued without replacing the electrode and the electrolyte, and repeated five times.

[0084] (4) Product testing

[0085] After two hours of constant potential electrolysis at a cell voltage of 1V, 300 microliters of electrolyte were extracted from the cathode and cathode of control group 1 and control group 2, 100 microliters of deuterated water, 200 microliters of water, and 50 microliters of DMSO (2mM) were added, and the mixture was placed in a nuclear magnetic resonance tube for nuclear magnetic resonance detection. The results of the detection and calculation are shown in the figure below. Fig.12 As shown, the lactic acid production in control group 2 is greater than that in control group 1, indicating that the rate of lactic acid production by anode-cathode coupling is greater than that by simple anode reaction, which means that the anode-cathode coupling strategy can improve energy utilization efficiency.

Claims

1. A method for preparing lactic acid by electrocatalytic cathode-cathode coupling, characterized in that: The following steps are involved: (1) Assembling an electrolytic cell: using the anode catalyst as the anode and the cathode catalyst as the cathode, placing the anode and the cathode in corresponding electrolytes respectively, and assembling an electrolytic cell; (2) Electrocatalytic reaction: 1,2-propylene glycol is added to both the anolyte and the catholyte. Under the application of a certain voltage, 1,2-propylene glycol is oxidized to lactic acid at the anode end. Oxygen is continuously introduced into the catholyte, and additional divalent iron compounds are added to the electrolyte to catalyze the formation of hydroxyl radicals, thereby achieving the electrochemical conversion of 1,2-propylene glycol and oxygen to produce lactic acid.

2. The method according to claim 1, characterized in that The anode catalyst is one of single metal / conductive substrate, bimetal / conductive substrate, bimetal / hydroxide, bimetal / oxide, or a combination of two or more thereof, wherein the hydroxide is one of nickel-based, cobalt-based, copper-based, and iron-based hydroxides; and the oxide is one of nickel oxide, cobalt oxide, iron oxide, and copper oxide.

3. The method according to claim 1, characterized in that The metal on the anode catalyst is one or a combination of two of platinum, gold, silver, ruthenium, palladium and copper.

4. The method according to claim 1, characterized in that The conductive substrate is one of carbon cloth, carbon paper, foam nickel, nickel mesh, foam copper and copper mesh.

5. The method according to claim 1, characterized in that: The divalent iron compound is at least one of ferrous sulfate, ferrous nitrate and ferrous oxalate.

6. The method according to claim 1, characterized in that The anolyte is any one aqueous solution of sodium hydroxide, potassium hydroxide, lithium hydroxide, potassium bicarbonate, potassium carbonate, sodium bicarbonate, and sodium carbonate, and the concentration is 0.1-2M.

7. The method according to claim 1, characterized in that The cathode electrolyte is at least one of perchloric acid, sulfuric acid, and sodium bisulfate solution, and the concentration is 0.1-1M.

8. The method according to claim 1, characterized in that: The conditions of the electrocatalytic reaction in step (2) are normal temperature and pressure, and the anode voltage is 0.3V to 1.5V vs. RHE.

9. The method according to claim 1, characterized in that: The concentration of the divalent iron compound applied in step (2) is 0.05 to 50 mM.

10. The method according to claim 1, characterized in that The oxygen flow rate introduced in step (2) is 10 to 50 mL / min.

Citation Information

Patent Citations

  • Method for preparing polyalcohol acid coupled hydrogen production from polyalcohol through electrocatalysis

    CN115896822A

  • Method and apparatus for producing hydroxy acid

    JP2021025066A

Cited By

  • Method for preparing lactic acid through electro-catalysis of acetylacetone

    CN121320996A